Sexualidade e velhice: as vozes dos idosos do ponto de vista da gerontologia social - Bitelli, Flavia Settanni Pinto Gonçalves (2014)
The myth that the old age is sexless was the main reason that led us to delineate this research, we aimed to identify the geriatric setting that people over 60 say about their sexuality in order to understand the social discourse of them. For geriatric scenario research for this academic Master Program of Postgraduate Studies in Gerontology at PUC - SP , the references are the TV Globo's soap operas and documentary films . Part of the selection of dissertations, totaling eight, was taken in the Digital Library of PUC - SP , which provides electronically academic productions defended since 2005 . A selection of previous works was held at the postgraduate program itself. Regarding the TV Globo soup operas, the analysis of these studies are part of currently developed in the research group certified by CNPq " Longevity , Aging and Communication " , which is part of the researcher . As for documentary films "The dance of life" and "69 Square Light" - have access to the same social network as a nominee of the researcher , available on the Internet . The survey results explained as the voices of people above 60 years, considering the multiplicity of approaches and narratives , revealing dense speeches of a taboo subject, which is sexuality in elderly. The appreciation of concepts expressed in those documents was also grounded in the concept of content analysis . Identifying some " experiences " highlighted the dissertations , serials and documentary films , as well as contribute to the reflection on the possible sexualities , from the " voices " of the elderly and their meanings , enabled better understand the wants in this life stage . It is understood that these narratives extend the concept of culture. So, if life is a trial of sexuality , highlighting the lines of those who experience it is to trace a possible aesthetic of old age , in which the experience of aging shows various sexual behaviors